INTRODUCTION TO THE DEVELOPMENT OF A HYDRAULIC ROAD BINDER BASED ON MINERAL COAL BOTTOM ASH - Mahamadou, Saley; Mahamadou, Issiakou; Abdoulatif, Abass Saley (My University, 2021)
The use of natural aggregates with suitable characteristics for road construction presents in some regions a real problem of availability or cost related to transport. However, the resources in place, which are naturally unusable, can be used after treatment with Hydraulic Road Binders (HRB). In this study, we propose to valorize the mineral Coal Bottom Ash (CBA), a residue from the combustion of the SONICHAR power station in Niger, as the main component of an HRB.After a physical, chemical and mineralogical characterizationof the coal bottom ash, several proportions of the CBA powder and a cement type CEM I 42.5 were studied. Compression tests were carried out at 07, 28, 56 and 90 days to determine the class of the binder corresponding to the mixture selected.The performance of the HRB thus obtained was evaluated on two types of weakly clay soils (IP <= 12, NF P 94-051), having an initially insufficient CBR. The 3% treatment of this product made the two aforementioned soils suitable for use as a base layer.
International Journal of Advanced Research, 9(02), 766-772
Keywords: Salaou Nourou; Garba Zibo; HYDRAULIC ROAD BINDER; MINERAL COAL BOTTOM ASH; EMIG (l’Ecole des Mines, de l’Industrie et de la Géologie); Université Abdou Moumouni